Cárie dentária em crianças de 5 anos: fatores sociodemográficos, lócus de controle e atitudes parentais - Nunes, Vinícius Humberto; Perosa, Gimol Benzaquen (ABRASCO - Associação Brasileira de Saúde Coletiva, 2017)
Abstract Dental decay affects many children, especially those from the lower socioeconomic classes. In this cross-sectional study designed to investigate the role played by sociodemographic factors, parental attitudes, and locus of control, which are an indicator of personal perception of what controls individual health, on the prevalence of tooth decay among 5-year-old pre-school children living in a midsized city in São Paulo, Brazil. The ceo-d index of 426 children was assessed; the parents reported sociodemographic characteristics and completed two questionnaires concerning locus of control and parental attitudes. The results show that 52.35% of the children had decay; higher levels of severe decay were observed among lower E-F socioeconomic classes. Higher socioeconomic status and low externality appear to be protective factors. Low parental internality emerged as a risk factor for decay in primary teeth, possibly because the mother expects or delegates the action to others, delaying care. Parental perceptions of control over a child's health seem to impact preventive care and, consequently, the level of tooth decay among children.

Resumo A cárie dentária afeta grande parte das crianças, principalmente as de baixo nível socioeconômico. Neste estudo, de delineamento transversal, objetivou-se investigar o papel de fatores sociodemográficos, atitudes parentais e do Lócus de Controle, indicador da percepção pessoal sobre o que controla a saúde do sujeito, na prevalência de cárie em pré-escolares de cinco anos, moradores de cidade de médio porte paulista. Avaliou-se o índice ceo-d de 426 crianças; os pais informaram sobre as características sociodemográficas, responderam a dois questionários de Lócus de Controle e um de atitudes parentais. Os resultados mostraram que 52,35% dos pré-escolares apresentaram cárie, com a severa em níveis mais altos nos estratos mais baixos E-F. Nível socioeconômico mais alto e baixa externalidade mostraram-se como fatores de proteção. Baixa internalidade parental apareceu como um fator de risco para cárie nos dentes decíduos, possivelmente porque a mãe espera ou delega a ação a outros, retardando os cuidados. A percepção parental de controle sobre a saúde do filho parece favorecer cuidados preventivos e, consequentemente, o nível de cárie da criança.
Dental decay in 5-year-old children: sociodemographic factors, locus of control and parental attitudes
Keywords: Dental decay; Oral health; Child care; Child health; Cárie dentária; Saúde bucal; Cuidado da criança; Saúde da criança